The Use of Information and Communication Technology (ICT) As a Learning Tool - Wulandari, Algusti; putra Viratama, Ika (Teunuleh Publisher, 2025)
The use of Information and Communication Technology (ICT) as a learning tool has transformed education by enhancing accessibility, flexibility, and engagement. This study employs a literature review method to analyze ICT implementation in learning media development. Data sources include journals, books, articles, and research reports. Findings indicate that ICT facilitates interactive and student-centered learning, enhances critical thinking, and expands educational resources. Additionally, ICT shifts the teacher’s role from an information provider to a facilitator. However, challenges such as digital literacy gaps, infrastructure limitations, and the potential for technology misuse hinder its optimal use. To maximize ICT’s effectiveness, adequate teacher training, curriculum integration, and policy support are essential. This study highlights trends, challenges, and opportunities in ICT-based education while emphasizing the need for further research on its impact and best practices. The findings serve as a foundation for future studies on technology integration in education.